2013
DOI: 10.3389/fnbeh.2013.00038
|View full text |Cite
|
Sign up to set email alerts
|

Robust training attenuates TBI-induced deficits in reference and working memory on the radial 8-arm maze

Abstract: Globally, it is estimated that nearly 10 million people sustain severe brain injuries leading to hospitalization and/or death every year. Amongst survivors, traumatic brain injury (TBI) results in a wide variety of physical, emotional and cognitive deficits. The most common cognitive deficit associated with TBI is memory loss, involving impairments in spatial reference and working memory. However, the majority of research thus far has characterized the deficits associated with TBI on either reference or workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…[3335]. After LFPI, working memory dysfunction follows a temporal evolution that is dependent on injury severity.…”
Section: Types Of Memory and Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…[3335]. After LFPI, working memory dysfunction follows a temporal evolution that is dependent on injury severity.…”
Section: Types Of Memory and Tbimentioning
confidence: 99%
“…A study with a radial arm maze showed impairment in memory retention after mild and moderate TBI up to 25 PID [35,37,5659]. Interesting, no deficits were observed when given a brief reminding procedural prompt [35,55].…”
Section: Types Of Memory and Tbimentioning
confidence: 99%
“…Our results indicate that using a weaker training protocol, like reducing the number of trials, is more sensitive than a massive training to identify differences in cognition after a CHI [38]. Reduction in the number of training per day reduced fatigue and stress in the animals.…”
Section: Discussionmentioning
confidence: 95%
“…Vascular dementia, including learning-memory impairment, is one of the most severe symptoms of brain injury and has attracted attentions of numerous doctors and researchers. 22,23 Water maze is widely used to evaluate the learning-memory function in many murine brain injury models. 24,25 Cognitive impairment after vascular dementia has been found the correspondingly pathological changes in brain, for examples increasing axon and myelin density in the corpus callosum and white matter bundles in the striatum, increasing oligodendrocyte and oligodendrocyte progenitor cell number in the corpus callosum, cortex and striatum and increasing synaptic protein expression in the cortex, striatum and hippocampus.…”
Section: Discussionsmentioning
confidence: 99%